12R‐lipoxygenase activity is reduced in photodamaged facial stratum corneum. A novel activity assay indicates a key function in corneocyte maturation. (28th May 2019) - Guneri, D.; Voegeli, R.; Munday, M. R.; Lane, M. E.; Rawlings, A. V.
Abstract: Background: During the late stage of keratinocyte differentiation, corneocytes gain a strong protein–lipid structure: the corneocyte envelopes (CE), composed of the inner corneocyte protein envelope (CPE) and the outer corneocyte lipid envelope (CLE). The hydrophobicity of CEs depends on the covalent attachment of linoleoyl‐acyl‐ceramides by transglutaminases (TG). These ceramides are processed by a range of other enzymes, including 12R‐lipoxygenase (12R‐LOX), before the covalent attachment of the free ω ‐hydroxyceramides to the CPE surface to form the CLE. The mechanical strength of CE is obtained with the formation of isodipeptide bonds by TG. The increase in hydrophobicity and rigidity leads to CE maturation which supports the integrity and mechanical resistance of the stratum corneum (SC). Objectives: The aim of this work was to develop and validate a novel enzyme activity assay for 12R‐LOX in tape strippings of photo‐exposed (PE) cheek and photo‐protected (PP) post‐auricular SC of healthy Chinese volunteers ( n  = 12; age 25 ± 3 years). Results: A fluorescence‐based assay was developed with ethyl linoleic acid as the substrate and a polyclonal antibody against 12R‐LOX as an inhibitor. The specificity was shown by the lack of effect by a LOX inhibitor (ML351) and an epidermal‐type lipoxygenase 3 (eLOX3) antibody on the acquired 12R‐LOX activity. Reduced 12R‐LOX activity was observed in the outer compared to the inner SC layers. Moreover, dramatically lower activity was shown in the PE vs. PP samples. Furthermore, the enzyme activity has a positive correlation ( r  = 0.94 ± 0.03) with CE maturity, in particular hydrophobicity, and a negative correlation ( r  = −0.96 ± 0.01) with transepidermal water loss (TEWL). Conclusion: This novel enzyme assay revealed a lower 12R‐LOX activity in tape strippings from PE cheek for the first time. This finding is in line with less mature CEs and higher TEWL compared to PP post‐auricular samples. This study indicates a strong link between 12R‐LOX activity and CE maturation and SC integrity. Abstract : 12R‐LOX and eLOX3 immunostaining of CEs from the first and ninth tape strippings of PE Cheek and PP post‐auricular sites with Nile red staining to visualize CLE, showing a strong signal in the deeper SC layers in both anatomical sites. Scale bar = 100 µm. Résumé: Contexte: Pendant le stade avancé de différenciation des kératinocytes, les cornéocytes acquièrent une solide structure protéines–lipides : l'enveloppe des cornéocytes (EC) composée de l'enveloppe protéinique des cornéocytes (EPC) interne et de l'enveloppe lipidique des cornéocytes (ELC) externe. L'hydrophobicité des EC dépend de la liaison covalente des linoléoyl‐acyle‐céramides par transglutaminases (TG). Ces céramides sont traités par un ensemble d'autres enzymes, y compris la 12R‐lipoxygénase (12R‐LOX), avant la liaison covalente des xhydroxycéramides à la surface de l'EPC pour former l'ELC. La force mécanique de l'EC est obtenue par la formation de liaisons isodipeptides par TG. L'augmentation de hydrophobicité et de la rigidité conduit à une maturation de l'EC qui soutient l'intégrité et la résistance mécanique de la couche cornée (stratum corneum, SC). Objectifs: L'objectif de ce travail était de développer et de valider un test novateur de l'activité enzymatique pour le 12R‐LOX par arrachage par bande sur une joue exposée à la lumière (photo‐exposed, PE) et sur de la SC à l'arrière de l'oreille protégée de la lumière (photo‐protected, PP) de volontaires sains chinois ( n  = 12; 25 ans ± 3 ans). Résultats: Un test de fluorescence a été développé avec de l'acide linoléique éthylique en tant que substrat et un anticorps polyclonal anti‐12R‐LOX en tant qu'inhibiteur. La spécificité a été démontrée par le manque d'effet d'un inhibiteur de LOX (ML351) et d'un anticorps anti‐lipoxygénase 3 (eLOX3) de type épidermique sur l'activité du 12R‐LOX acquise. Une réduction de l'activité du 12R‐LOX a été observée dans les couches de SC externes par rapport aux couches internes. En outre, une activité considérablement plus faible a été démontrée dans les échantillons PE par rapport aux échantillons PP. De plus, l'activité enzymatique a une corrélation positive ( r  = 0, 94 ± 0, 03) avec la maturité de l'EC, en particulier l'hydrophobicité, et une corrélation négative ( r  = −0, 96 ± 0, 01) avec une perte d'eau transépidermique (transepidermal water los, TEWL). Conclusion: Ce dosage enzymatique novateur, à partir de tape stripping sur les joues exposée à la lumière, a révélé une activité 12RLOX plus faible pour la première fois. Cette découverte est cohérente avec des EC moins matures et une TEWL plus élevée par rapport aux échantillons PP de l'arrière de l'oreille. Cette étude indique un lien solide entre l'activité du 12R‐LOX et la maturation de l'EC et l'intégrité de la SC.